2023
DOI: 10.5409/wjcp.v12.i3.151
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastroesophageal reflux disease in children with extraesophageal manifestations using combined-video, multichannel intraluminal impedance-pH study

Abstract: BACKGROUND Gastroesophageal reflux disease (GERD) might be either a cause or comorbidity in children with extraesophageal problems especially as refractory respiratory symptoms, without any best methods or criterion for diagnosing it in children. AIM To evaluate the prevalence of extraesophageal GERD using conventional and combined-video, multichannel intraluminal impedance-pH (MII-pH), and to propose novel diagnostic parameters. METHODS The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Our findings underscore the diagnostic utility of pH-MII monitoring in preschool children with recurrent wheezing, revealing a significantly higher proportion of GERD compared to pH-metry alone. This aligns with recent studies that have emphasized the limitations of pH-metry in detecting WAR [14][15][16][17], further highlighting the importance of pH-MII in providing a more accurate representation of reflux events and their associations with clinical symptoms. Notably, we observed that GERD was diagnosed in 71% of cases using pH-MII compared to only 12% with pH-metry alone.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings underscore the diagnostic utility of pH-MII monitoring in preschool children with recurrent wheezing, revealing a significantly higher proportion of GERD compared to pH-metry alone. This aligns with recent studies that have emphasized the limitations of pH-metry in detecting WAR [14][15][16][17], further highlighting the importance of pH-MII in providing a more accurate representation of reflux events and their associations with clinical symptoms. Notably, we observed that GERD was diagnosed in 71% of cases using pH-MII compared to only 12% with pH-metry alone.…”
Section: Discussionsupporting
confidence: 86%
“…Eiamkulbutr et al [ 25 ] described MNBI as having a good discriminatory ability to diagnose GERD, with an area under the curve (AUC) of 0.726 (95% CI: 0.581–0.870). The study identified a cutoff value of 1466 ohms for MNBI, yielding a sensitivity of 50.0% and a specificity of 33.33%.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their promise, the utility of the PSPW index and MNBI in pediatric GERD remains incompletely understood. While studies in adult populations have demonstrated their potential diagnostic value, the pediatric population presents unique challenges and considerations that may influence the applicability and interpretation of these metrics [ 25 ]. As such, a comprehensive evaluation of the existing literature is warranted to assess the evidence supporting the use of the PSPW index and MNBI in diagnosing GERD in children.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of GERD is difficult to establish because of the heterogeneity of the diagnostic criteria used in different studies [ 3 , 4 , 5 ]. The disease could occur in 25.5% of babies aged 0–1 month, decreasing to 1.1–1.6% by 1 year of age [ 3 , 5 ] and ranging from 0.9% to 18.8% [ 5 , 6 ] in childhood and adolescence.…”
Section: Introductionmentioning
confidence: 99%